Novel VPS33B mutation in a patient with autosomal recessive keratoderma‐ichthyosis‐deafness syndrome. Issue 12 (18th December 2018) - Alter, Svenja; Hotz, Alrun; Jahn, Arne; Di Donato, Nataliya; Schröck, Evelin; Smitka, Martin; von der Hagen, Maja; Schallner, Jens; Menschikowski, Mario; Gillitzer, Claus; Laass, Martin W.; Fischer, Judith; et al.
Abstract : Autosomal recessive keratoderma‐ichthyosis‐deafness (ARKID) syndrome is a rare multisystem disorder caused by biallelic mutations in VPS33B ; only three patients have been reported to date. ARKID syndrome is allelic to arthrogryposis‐renal dysfunction‐cholestasis (ARC) syndrome (MIM #208085), a severe disorder with early lethality whose phenotypic characteristics also include ichthyosis, hearing loss, severe failure to thrive, platelet dysfunction and osteopenia. We report on an 11‐year‐old male patient with ARKID syndrome and compound heterozygous VPS33B mutations, one of which [c.1440delG; p.(Arg481Glyfs*11)] was novel. Clinical features of this patient included ichthyosis, palmoplantar keratosis, hearing loss, intellectual disability, unilateral hip dislocation, microcephaly and short stature. He also had copper hepatopathy and exocrine pancreatic insufficiency, features that have so far been associated with neither ARKID nor ARC syndrome. The patient broadens the clinical and molecular spectrum of ARKID syndrome and contributes to genotype–phenotype associations of this rare disorder.